Immortal beloved [videorecording (DVD)] - Rose, Bernard, 1961-; Oldman, Gary; Krabbé, Jeroen, 1944-; Rossellini, Isabella (Columbia TriStar Home Video, 2000)
Based on the life of composer Ludwig Beethoven. A letter found after his death leads to efforts to uncover the mystery of who was his immortal beloved.